Production Cross-Section Measurements for Terbium Radionuclides of Medical Interest Produced in Tantalum Targets Irradiated by 0.3 to 1.7 GeV Protons and Corresponding Thick Target Yield Calculations - Duchemin, Charlotte; Cocolios, Thomas E.; Dockx, Kristof; Farooq-Smith, Gregory J.; Felden, Olaf; Formento-Cavaier, Roberto; Gebel, Ralf; Köster, Ulli; Neumaier, Bernd; Scholten, Bernhard; Spahn, Ingo; Spellerberg, Stefan; et al. (Frontiers in Medicine, 2021)
This work presents the production cross-sections of Ce, Tb and Dy radionuclides produced by 300 MeV to 1.7 GeV proton-induced spallation reactions in thin tantalum targets as well as the related Thick Target production Yield (TTY) values and ratios. The motivation is to optimize the production of terbium radionuclides for medical applications and to find out at which energy the purity of the collection by mass separation would be highest. For that purpose, activation experiments were performed using the COSY synchrotron at FZ Jülich utilizing the stacked-foils technique and γ spectrometry with high-purity germanium detectors. The Al-27(p,x)Na-24 reaction has been used as monitor reaction. All experimental data have been systematically compared with the existing literature.